Factors Related to The Level of Dietary Adherence in The Elderly with Type 2 Diabetes Mellitus - Fruine Violica Luna Vindra; Sri Ratna Rahayu (Universitas Negeri Semarang, 2025)
Type 2 diabetes mellitus is the most common type, especially in the elderly. Older people are more at risk of experiencing elevated blood sugar levels, so they are strongly encouraged to adhere to diet therapy to control their blood sugar levels. However, 85% of older adults with diabetes who conduct examinations at the Tlogosari Wetan Health Center have uncontrolled blood sugar levels caused by poor diet. This study aimed to determine the factors associated with dietary compliance in older adults with type 2 diabetes mellitus at the Tlogosari Wetan Health Center. This type of research is observational analytic research with a cross-sectional approach. The number of samples in this study was 61 respondents who were taken using a purposive sampling technique. The data analysis used was univariate analysis and bivariate analysis. The results showed that there was a relationship between the duration of type 2 diabetes mellitus (p value = 0.036), the level of knowledge (p value = 0.014), the frequency of participation in nutrition counseling (p value = 0.022) and the level of family support (p value = 0.023) with the level of dietary compliance in older adults with type 2 diabetes mellitus at Tlogosari Wetan Health Center. There is no relationship between gender (p value = 1.000), education level (p value = 0.421), and the level of support from health workers (p value = 0.343) with the level of dietary compliance in older adults with type 2 diabetes mellitus at the Tlogosari Wetan Health Center.